2016
DOI: 10.1149/2.1061614jes
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Dissolution of Aluminum in the Aluminum Chloride-1-Ethyl-3-methylimidazolium Chloride Ionic Liquid

Abstract: The anodic dissolution of aluminum metal was investigated in the Lewis acidic chloroaluminate ionic liquid, aluminum chloride-1-ethyl-3-methylimidazolium chloride. The investigation was conducted on aluminum rotating disk electrodes as a function of potential, ionic liquid composition, and temperature. Two different dissolution mechanisms were realized. At modest overpotentials, dissolution takes place under mixed kinetic-mass transport control. However, as the overpotential is increased to induce higher disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
(60 reference statements)
4
20
1
Order By: Relevance
“…From the ex situ/in situ tests and thermodynamic-based analysis, it was found that a key parameter to control growth of the inert oxide film is the surface tension, which could be controlled by using proper amount of chloride ions in the electrolyte, and the cracks were formed on the oxide film by 21% when it was submerged into the electrolyte of molar ratio 1:1.5 of [EmIm]Cl and AlCl 3 , which is the electrolyte condition utilized in most research [7,19,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the ex situ/in situ tests and thermodynamic-based analysis, it was found that a key parameter to control growth of the inert oxide film is the surface tension, which could be controlled by using proper amount of chloride ions in the electrolyte, and the cracks were formed on the oxide film by 21% when it was submerged into the electrolyte of molar ratio 1:1.5 of [EmIm]Cl and AlCl 3 , which is the electrolyte condition utilized in most research [7,19,33].…”
Section: Discussionmentioning
confidence: 99%
“…However, the OCV decreased significantly at the ratio of 1:2, which may be interpreted as the direct effect of Clion (i.e., corrosion) on the active area of the Al electrode, and the Clion affected not only the oxide film but also the Al active area. It is reported that at the ionic liquid ratio of 1:0.5, the dominant chloro-aluminate species in the electrolyte is AlCl4 - [7,8,19,33]. As the ratio of AlCl3 is increased from 1:0.5 to 1:1.5, the ionic liquid contains AlCl4 -and Al2Cl7 -species.…”
Section: Effect Of Chloride Ion Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In both ionic liquid systems, the Al anodization reaction is under mixed kinetic/mass-transport control at moderate overpotentials, but becomes a mass transport-limited process governed by the dissolution of a passive layer of solid AlCl 3 on the anode at more positive overpotentials. 55,56 Not surprisingly, in consideration of the reaction in Eq. 1, the anodic process is favored in slightly acidic melts, but highly disfavored under very acidic conditions.…”
mentioning
confidence: 99%
“…Upon dissolution of iron, free chlorides are available making the passivation of iron by FeCl 2 very unlikely. The passivation of metals is reported in acidic chlorometallate ionic liquids (MCl 3 –ionic liquid mole ratio >0.50) 8385. In Lewis-acidic ionic liquids the activity of free chlorides is insignificant.…”
Section: Resultsmentioning
confidence: 99%